Penyuluhan Tentang Pentingnya Air Bersih Dan Standar Air Minum Yang Sehat Untuk Menjaga Kesehatan Pencernaan Dan Tetap Bugar - Augustinus Robin Butarbutar (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Digestive health plays a central role in maintaining overall individual well-being. Consuming clean water that meets healthy drinking water standards is a key factor in maintaining digestive health. Education on the importance of clean water and healthy drinking water standards is conducted to increase public awareness of the positive impact of water on digestive health and overall body well-being. Through these educational efforts, it is hoped that the public can understand the urgency of drinking clean water that meets health standards as an effort to maintain digestive health and body vitality. The educational approach used includes information dissemination, demonstration, and interactive discussions to create comprehensive and sustainable understanding. In conclusion, educational efforts regarding the importance of clean water and healthy drinking water standards are crucial steps in improving digestive health and overall community well-being.